Application of African Customary Law: Tracing its Degradation and Analysing the Challenges it Confronts - Owino, Lisa (Strathmore Law Review, 2016)
Historically, African customary law has occupied the lower rungs of the legal ladder, often being set aside for more formal laws. This is primarily due to the introduction of western and religious legal systems through the exploration of western nations into Africa, missionary activity and, subsequently, colonisation. However, African countries – including Kenya – are making an effort to give due recognition to customary law. This paper discusses the steady degradation of customary law from the colonial period to the promulgation of the Constitution of Kenya 2010 where there are attempts to resuscitate its application, it also discusses the challenges that the courts may face in this application of customary law today and possible solutions to these challenges.